Drawing the threads together: How emerging technologies can help integrate the health care needs of children and young people in out-of-home care - Usher, Helen-Louise; Mills, Ryan; Moss, Perrin; Tracey, Frank (International journal of integrated care, 2018)
Introduction: This presentation describes the progress of the "Children and Young People in Out-of-Home Care Innovation Fund Integrated Care " project currently being undertaken by Children's Health Queensland.Children and young people in out-of-home care (OOHC) are subject to many levels of disadvantage including socio-economic disadvantage and trauma. In comparison to the general population, they experience poorer mental and physical health outcomes in childhood and adolescence, which continue into adulthood. There are more than 8000 children and young people in OOHC in Queensland. There is a recognised lack of coordination in their health care. The young people, their carers and the Child Safety workers negotiate a fragmented system - primary versus specialist care, and public versus private services - without clear roles and responsibilities among providers, and lacking oversight of each young person's health management. Paediatricians have historically taken a lead role in advocating for this vulnerable group of young people, however, the health needs of this group are diverse and primary care is positioned to be the first site of comprehensive assessment in a tiered approach, supported by the expertise of paediatricians and other staff within Hospital and Health Service child protection units.Practice Change: This project is developing an integrated system of health assessment and management for children and young people in OOHC that maximises the input of the primary sector, while allowing efficient digital communication between primary and tertiary care providers.The specific innovative elements of this project are: Pioneering collaboration between primary health care and Queensland Health settings at a level of engagement that has not been attempted or achieved previously.Development of a secure, shared digital platform for the documentation of the young person’s health status, with integrated multi-user management planning capability.Scalability of the piloted system to other groups of paediatric patients and across the State.Aim and Theory of Change: The aim of this project is to create an infrastructure and clinical tools to support the co-ordinated health assessment and management of children and young people in out-of-home care.Targeted Population: Children and Young people in out-of-home care residing in the Brisbane region are being targeted for this study.Stakeholders: Key Stakeholders include Department of Communities, Child Safety and Disability Services; Aboriginal & Torres Strait Islander Community Health Service; participating general practices and individual practitioners; and hospital Child Protection Units and Paediatricians.Timeline: the project commenced January 2017 and has a projected end date of June 2019.Sustainability: After initial set-up costs, efficiencies in health service utilisation and worker capacity will be immediate, and sustainable over the long term.Transferability: The platform will be built with the view to scaling the project across the state. Furthermore, the integrated information technology system will be scalable to many different groups of clients across the health system.Conclusions: Project progress will be discussed including the successful collaboration between the stakeholders and early development of the clinical tools. Delays include the complexities involved in building the integrated information technology system. A successful parallel project will also be highlighted.